Optimalisasi Branding Produk UMKM Ibu-ibu PKK Desa Simogirang melalui Pemanfaatan Media Sosial dan Teknologi Internet - Rony Kriswibowo; Mohammad Fathoni; Rusina Widha Febriana; Johan Suryo Prayogo; Purwanto Purwanto; M. Shodikin; Putri Ariatna Alia (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This community service initiative was designed to improve the digital competence of the PKK (Family Welfare Empowerment) group in Simogirang Village, Prambon Sub-district, Sidoarjo Regency, with a focus on utilizing social media and internet-based tools to optimize the branding of local UMKM (Micro, Small, and Medium Enterprises) products. The program adopted an andragogical approach that emphasizes adult learning, integrating methods such as direct instruction, hands-on demonstrations, and guided simulations. Key digital platforms including Instagram, WhatsApp Business, Google Docs, and Google Drive were introduced and practiced during the sessions. A total of 40 participants took part in the training. Evaluation results indicated that 85% of the participants successfully mastered the digital branding techniques, achieving over 85% accuracy in practical exercises. This achievement was evidenced by the creation of functioning business accounts, digital catalogs, and various forms of promotional content tailored to their UMKM products. The implementation of these digital tools led to a noticeable increase in consumer engagement and demand for village products, particularly cassava chips and handmade crafts, signifying a positive impact on local economic activities. To ensure long-term benefits and continuous improvement, a dedicated WhatsApp group was established as a support forum for participants to share experiences, ask questions, and receive guidance post-training. Despite its success, the initiative faced challenges related to unstable internet infrastructure in certain areas of the village, highlighting the need for improved digital access. In conclusion, this initiative not only enhanced the digital literacy of rural women but also contributed to their economic empowerment, aligning with broader efforts to promote smart village development and digital transformation in rural Indonesia.